Construction materials : their nature and behaviour - Soutsos, Marios; Domone, P. L. J. (CRC Press, 2018)
This established textbook provides an understanding of materials' behaviour through knowledge of their chemical and physical structure. It covers the main classes of construction materials: metals, concrete, other ceramics (including bricks and masonry), polymers, fibre composites, bituminous materials, timber, and glass.
Keywords: Building materials.; elektronické knihy; electronic books